Ice Breaking: Implementasi, Manfaat dan Kendalanya untuk Meningkatkan Konsentrasi Belajar Siswa - Marzatifa, Leta; Agustina, Maya; Inayatillah, Inayatillah (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2021)
Boredom in the teaching and learning process is very often occurring, especially in elementary school-aged children, this can be understood because, their age in the playing period. So to overcome the boredom, teachers need to know some ice-breaking methods. The purpose of writing this article is to find out the application of ice breaking and its relationship to the return of student learning concentration as well as the obstacles faced by teachers in the application of ice breaking. This type of research is a literature study. Teknik data collection used is documentation. The data analysis technique used is an analysis article. The results showed that (1) icebreaking can be applied to all subjects even in student tutoring services. Ice Breaking can be combined with learning methods such as joyful learning methods or other game techniques (2) because after doing these activities, the concentration of student learning becomes good and can stimulate student absorption, learning interests, learning attention, learning outcomes and can foster student learning spirit (3) Obstacles faced include teachers less mastery of types of ice breaking, less creative, and charcoal there is soft skill training based on ice-breaking